A journey of 1000 miles begins with a passionate team - Yang, Hao Lin (Nanyang Technological University, 2023)
As a producer, I have been on many film sets, but this journey, this 1400KM journey in making ‘How Long Is Now’, was different. From the moment we read the script, and we started off the ride in Malaysia, we knew that we were embarking on something special. We were pushing boundaries, exploring new cultures, and forging fond relationships that will last a lifetime.